Pengukuran tingkat kapabilitas rekam medis elektronik menggunakan COBIT 2019 - Fariz Satya Hadi; Tria Saras Pertiwi; Hosizah Hosizah; Imam Sutanto (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: The development of digital transformation in the healthcare sector has driven the importance of structured IT asset management, particularly in the implementation of electronic medical records (EMD) systems. Purpose: To analyze the capability level of the BAI09 (manage assets) process in the implementation of an EMR in a hospital using the COBIT 2019 framework. Method: This descriptive quantitative study used a case study approach on the implementation of an EMR at Bhakti Mulia Hospital. The research focused on measuring the capability level of IT asset management using the COBIT 2019 framework in the BAI09 (manage assets) domain. The analysis was conducted by measuring capability levels based on the COBIT 2019 model, covering Levels 0 to 5. The resulting data were used as the basis for a descriptive evaluation to develop recommendations for improvements and enhance IT asset management capabilities in the EMR. Results: The capability level of the BAI09 process was at Level 3 (established process) with an achievement rate of 100%, indicating that the IT asset management process has been documented and consistently implemented. Meanwhile, achievement at Level 4 (predictable process) remains at 75%, or largely achieved. Consequently, the implementation of data-based performance measurement and monitoring has not been optimally implemented. Gaps identified include the lack of key performance indicators (KPIs), a real-time asset monitoring system, and an integrated software license audit mechanism. Conclusion: Measuring the capability level of information technology asset management in electronic medical records (EMD) systems using the COBIT 2019 framework in domain BAI09 (manage assets) is quite effective in providing an overview of the organization's capability level. A capability level reaching Level 3 (established process) indicates that the asset management process has clear procedures, is well-documented, and is consistently implemented to support the operation of the EMR system. Suggestion: Future research could expand the scope of the evaluation by including more domains within the COBIT 2019 framework to obtain a more comprehensive picture of information technology governance. Keywords: Asset Management; BAI09; Capability Level; COBIT 2019; Electronic Medical Record.